Konsep Asnaf Fī Sabilillah: Kajian Komparatif Pendapat Ulama Salaf dan Kontemporer - Lukmanul Hakim (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2020)
Abstract Fi sabilillah, is the multi-concept of mustahik zakat asnaf. Different from the other seven asnaf, fi sabilillah seems global and it is not clear to whom and what it is aimed at. Literally, the word fi sabilillah which means in the way of Allah needs a companion who explains the meaning. This paper is a comparative study of the opinions of salaf and contemporary ulama in interpreting asnaf fi sabilillah. Based on literature review, it can be concluded that the concept of fi sabilillah has experienced dynamics now. Through the legitimacy of ijtihad, contemporary ulama try to find the solution so that the concept can embrace Muslims who should be able to receive zakat through the mustahik zakat asnaf fi sabilillah, so that this concept does not experience stiffness in the current developing era. Keywords: Zakat, Mustahik, Fi sabilillah,